Multiscale causal networks identify VGF as a key regulator of Alzheimer’s disease - Noam D. Beckmann (Nature Portfolio, 2020)
To investigate the molecular foundation of sporadic Alzheimer’s disease (AD), Beckmann et al. constructed multiscale causal networks on a large human AD multi-omics dataset, detecting AD-associated networks and their top predicted regulator, VGF, with extensive validation in the 5xFAD mouse model.